Adaptability in an agent-based virtual organisation. (6th March 2009) - Frackowiak, G.; Ganzha, M.; Gawinecki, M.; Paprzycki, M.; Szymczak, M.; Badica, C.; Han, Yo-Sub; Park, Myon-Woong
In this paper we consider the adaptability in an agent-based Virtual Organisation (VO). After introducing the system and the need for adaptive behaviours, human resource adaptability in particular, we discuss how the goal of 'agent adaptation' can be implemented. Specifically, we propose how agent behaviours can be added into/removed from/replaced in an agent skeleton, and, in this way, agent functionality modified.